Non-functional alpha-cell hyperplasia with glucagon-producing NET: a case report - Cidade-Rodrigues, Catarina; Santos, Ana Paula; Calheiros, Raquel; Santos, Sara; Matos, Catarina; Moreira, Ana Paula; Inácio, Isabel; Souteiro, Pedro; Oliveira, Joana; Jácome, Manuel; Pereira, Sofia S.; Henrique, Rui; et al. (Frontiers in Endocrinology, 2024)
Alpha-cell hyperplasia (ACH) is a rare pancreatic endocrine condition. Three types of ACH have been described: functional or nonglucagonoma hyperglucagonemic glucagonoma syndrome, reactive or secondary to defective glucagon signaling and non-functional. Few cases of ACH with concomitant pancreatic neuroendocrine tumours (pNET) have been reported and its aetiology remains poorly understood. A case report of non-functional ACH with glucagon-producing NET is herein presented.A 72-year-old male was referred to our institution for a 2 cm single pNET incidentally found during imaging workout for acute cholecystitis. Patient past medical history included type 2 diabetes (T2D) diagnosed 12 years earlier, for which he was under metformin, dapagliflozin and semaglutide. The pNET was clinically and biochemically non-functioning, apart from mildly elevated glucagon 217 pg/ml (<209), and 68 Ga-SSTR PET/CT positive uptake was only found at the pancreatic tail (SUVmax 11.45). The patient underwent a caudal pancreatectomy and the post-operative 68 Ga-SSTR PET/CT was negative. A multifocal well-differentiated NET G1, pT1N0M0R0 (mf) strongly staining for glucagon on a background neuroendocrine alpha-cell hyperplasia with some degree of acinar fibrosis, was identified on pathology analysis.This case reports the incidental finding of a clinically non-functioning pNET in a patient with T2D and elevated glucagon levels, unexpectedly diagnosed as glucagon-producing NET and ACH. A high level of suspicion was required to conduct the glucagon immunostaining, which is not part of the pathology routine for a clinically non-functioning pNET, and was key for the diagnosis that otherwise would have been missed. This case highlights, the need for considering the diagnosis of glucagon-producing pNET on an ACH background, even in the absence of glucagonoma syndrome.